Metabolomic markers for agronomic traits and their possible biochemical mechanisms in black tea Camellia sinensis (L.) O. Kuntze - Apostolides, Zeno (University of Pretoria, 2021)
Thesis (PhD (Biochemistry))--University of Pretoria, 2021.